A general overview on the concep of westernalization in ottoman harboring culture - Akbaş, Gamze; Erdemir, Zuhal; Tosun, Zuhal; ERÇETİN, ARZU (My University, 2020)
The time frame of this study corresponds to an era which was questioned in a socio-political sense and accordingly in which a change was inevitable. In this direction, the radical change that the Empire passed through reveals a need of handling new understandings attributed to education, family and women as a whole. Therefore, in this study, many changes occurred in the social structure of the society along with the modernization process will be analyzed culturally and socially. In this course started with westernization, the Ottoman social structure started to change; and accordingly the Western culture data embarked upon to get involved in harboring culture. The increasing economic and political relations between Ottoman and Western caused Ottoman society to change its shell in social and cultural sense. In architectural historiography, when we reduce housing to the scope of Ottoman harboring culture, we see that the discourses are not polyphonic, rather, we can say that there is an ongoing time-wise reading on in the frame of same determinations. This analysis is mainly for naming problem, root concept, typology and spatial organization. Especially in researches on Ottoman harboring culture, it is seen that especially the naming issue turned into a problem. On the basis of all this data, a general overview on the Westernization effect on Ottoman harboring culture will be earned out.
Keywords: Architectural Historiography; Ottoman Society; Westernization; Culture; Mimari Tarihçilik; Osmanlı Topluluğu; Batılılaşma; Kültür